Elite sports schools: An international review - Radtke, S.; Coalter, F. (3rd Dimensions of Performance seminar "Elite Schools of Sport - Learning to Win", 2007)
• Point of departure & Aim of the study • Research approaches & Methods • International review: Schooling issues • International review: Sporting issues • Conclusion & Implications: Policy-relevant analysis